Supraclavicular Approach of Lobectomy Improves Quality of Life for Patients With Unilateral Papillary Thyroid Microcarcinoma: A Prospective Cohort Study - Xue, Shuai; Wang, Qiuli; Chen, Guang; Wang, Peisong; Zhang, Li (Frontiers in Endocrinology, 2022)
Abstract: Objective: Postoperative neck symptoms, including pain, swelling, uncomfortable feelings during swallowing, and incision adhesion formation are common in patients after lobectomy through traditional middle neck approach. A new unilateral supraclavicular approach is proposed to protect anterior cervical region and reduce related complications. The aim of this study is to investigate the efficacy, safety and advantages of supraclavicular approach in lobectomy for unilateral papillary thyroid microcarcinoma (PTMC). Methods:Two hundred sixty-three patients were recruited into either a conventional middle group (CM) or a new supraclavicular (NS) group. Clinicopathological features, surgically-related variables and postoperative symptoms were recorded. Quality of life (QOL) of all patients was assessed by the 12-item short-form health survey (SF-12) and thyroid cancer-specific quality of life (THYCA-QoL) questionnaire in 3 and 12 months. Results:There were no statistically significant differences in clinicopathological features (including sex, age, multifocality, extrathyroidal extension, histological variants, largest tumor diameter, Hashimoto’s thyroiditis, metastasized central lymph node, removed central lymph node, surgeon, BRAF mutation and follow-up duration), hospitalization (including hospital cost, surgery time and blood loss during surgery) and complications between the two groups. Patients underwent lobectomy through NS approach had significantly better SF-12 physical, mental and THYCA QOL than CM group patients both in 3 and 12 months (all p<0.001). Moreover, the NS group had a shorter hospitalization time. Conclusion:In conclusion, the NS approach for lobectomy is a safe and effective method for reducing postoperative symptoms and increasing QOL in patients with unilateral PTMC in both 3 and 12 months follow up.